PLANNING AND IMPLEMENTATION OF ODOO ERP HUMAN RESOURCE APPLICATION MODULE USING ACCELERATED SAP (ASAP) METHOD IN HEAVY EQUIPMENT RENTAL COMPANY - Affandy Affandy; Suryarini Widodo; Syti Sarah (Indonesian Journal of Multidisciplinary Science, 2022)
An integrated information system in the Human Resources Department (HRD) is needed for good HR management to improve employee performance. The Importance of Odoo ERP Implementation Human Resource Application Module to replace a system that uses excel sheets into an automation process in the employee payroll process according to the company's business processes. Based on these problems, research was conducted to plan and implement this module using the Accelerated SAP (ASAP) method. The ASAP method is a framework method that is applied to project management to improve efficiency in the implementation of Odoo ERP. The results of this study are the renewal of the business process for employee payroll with changes in the division of labor between actors in HRD and the Accounting & Finance Department. In addition, customization and configuration of the Human Resource Application module was carried out according to the payroll process business blueprint. The process of testing this application uses the Black Box Testing method which is focused on functional specifications.